2011
DOI: 10.1002/bem.20686
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in cultured human umbilical vein endothelial cells exposed to a 300 mT static magnetic field

Abstract: In a previous investigation we reported that exposure to a moderate (300 mT) static magnetic field (SMF) causes transient DNA damage and promotes mitochondrial biogenesis in human umbilical vein endothelial cells (HUVECs). To better understand the response of HUVECs to the 300 mT SMF, a high-quality subtracted cDNA library representative of genes induced in cells after 4 h of static magnetic exposure was constructed. The global gene expression profile showed that several genes were induced after the SMF exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…Similar results have been reported by Wan et al [2017]. There also were reports that the magnetic field induced the relative expression levels of genes involved in cell growth, metabolism, oxidative stress response, and protein synthesis [Cambpbell‐Beachler et al, 1998; Polidori et al, 2012]. Meanwhile, no obvious difference in the content of secondary metabolites was detected at 0.9 or 2.0 mT LF‐MF compared with the control.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results have been reported by Wan et al [2017]. There also were reports that the magnetic field induced the relative expression levels of genes involved in cell growth, metabolism, oxidative stress response, and protein synthesis [Cambpbell‐Beachler et al, 1998; Polidori et al, 2012]. Meanwhile, no obvious difference in the content of secondary metabolites was detected at 0.9 or 2.0 mT LF‐MF compared with the control.…”
Section: Discussionsupporting
confidence: 87%
“…Some cell cycle genes were upregulated by the LI‐EMF treatment, which probably contributed to the increased biomass. Polidori et al [] also reported that several genes involved in cell growth and division were upregulated by SMF (300 mT) in cultured human umbilical vein endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gravitational and MF variations are synergized to cause global transcriptional changes of Arabidopsis in in vitro callus cultures, mainly on structural, abiotic stress genes, and secondary metabolism genes [Manzano et al, ]. The gene expression profile of cultured human umbilical vein endothelial cells induced by a 300 mT static magnetic field (SMF) indicates that the cells are involved in cell metabolism, energy, cell growth/division, transcription, protein synthesis, destination and storage, membrane injury, DNA damage/repair, and oxidative stress response [Polidori et al, ]. Gao et al [] reported that a strong SMF (14.1 T) changed the expression of 65 genes involved in processes ranging from amino acid synthesis and DNA and energy metabolism to transcription and regulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…pump is regulated by protein phosphatases (PPases) and protein kinases A and G (PKA and PKG) (Therien and Blostein 2000;Ramnanan and Storey 2006). SMF-induced changes from literature are up-and downregulation of genes involved in cellular metabolism (Fos, Rbx1, BioB genes), membrane injury (Plscr 1 gene) (Wang et al 2009;Polidori et al 2012); reduction of mitochondrial DNA content and increase of reactive oxygen species (ROS) (Potenza et al 2010); activation of ERK signaling cascade (Prina-Mello et al 2006); inactivation of voltage-gated potassium and calcium channels (VGPC, VGCC, respectively) (Jie-Fei et al 2007;Rosen 1996); induction of an increase and decrease in [Ca 2? ] i ions (Prina-Mello et al 2006;Wang et al 2010) to the lower effective dose at the target tissue used in a number of randomized control trials of the therapeutic applications of magnetic fields for pain management, whereas a strength field of 100 mT was used in promising cell culture studies for Parkinson's disease treatment (Harlow et al 2004;Wolsko et al 2004;Wang et al 2010).…”
Section: Fos Plscr1mentioning
confidence: 99%